The legal meaning of Lefebvre’s the right to the city: addressing the gap between global campaign and scholarly debate - (:unkn) unknown (Springer, 2017)
There is a growing consideration globally of a right to the city in urban policies, strategies and legislation. The mention of this concept in the UN’s New Urban Agenda vision statement, in relation to human rights, both acknowledges and encourages this trend. It is also a result of lobbying and contestation. In the Anglo-American scholarly literature, there has been caution as to whether Henri Lefebvre intended a legal and institutionalized meaning for his ‘right to the city’. This paper reviews these debates and from that perspective examines Lefebvre’s positions on law, rights and the right to the city. It locates this within his wider political strategy and in particular the three-pronged strategy he put forward in The Urban Revolution to address the urban question – political foregrounding of the urban, promotion of self-management, and introduction of the right to the city into a transformed contractual system. By contextualizing and reviewing Everyday Life in the Modern World (published immediately before Right to the City), the paper examines Lefebvre’s thinking on rights formation, within ‘opening’, or the process of inducing change. The paper engages with meanings Lefebvre provides for rights in his concept of the right to the city, including his later conception of a contract of citizenship. The paper suggests that engagement with a fluid role of law and rights, in combination with Lefebvre’s other strategies, is important in opening the pathway he charts for the realization of this right, whether through local or global initiatives.
This paper examines Lefebvre’s positions on law, rights and the right to the city
Keywords: Lefebvre, Henri; New urban agenda; Rights; Rights to the city; Legal meaning